Ammonia-N removal using soil mixed culture:kinetic - Suryati, Mohd Mokhtar (2013)
Ammonia is a colorless,water-soluble gas by-product of the microbiological decomposition of organic nitrogen by the nitrification process.This ammonia is a natural chemical substance that contains inside the earth which can cause disturbance to living organism especially animals.The most affected animal due to this toxic gas is poultry which is in the industry.In Poultry Farm Wastewater(PFW),there contains a lot of ammonia-N(NH3)compound which is excreted by poultry.This high concentration of ammonia-N compound will produce a high level of toxic gas that will cause the poultry to be unhealthy or worst which is mortality.Since poultry is a source of food for people around the world, thus maintaining the quality of poultry is necessary.The high demand of poultry around the world nowadays leads to find a way to reduce the mortality of the poultry in industries.In order to reduce the mortality of poultry,a new way in reducing of ammonia-N in PFW in industries is needed in which by using soil mixed culture.There are some researches that have been found to use soil mixed culture as a medium of reducing this ammonia-N concentration inside this PFW.In this research,the objective is to study the kinetic parameter involving ammonia-N removal by using soil mixed culture. DR/2800 HACH Spectrometer will be utilized in order to determine concentration of ammonia-N.Since reduction of ammonia-N concentration is the one of the objective of this research,the determination of the best kinetic parameter for this soil mixed culture is required. An ammonia-N solution will be prepared by taking the pure ammonia-N solution mixed with water to get the solution. Kinetic parameter will be determined by ammonia-N removal using the soil mixed culture from University Malaysia Pahang (UMP)and poultry farm in which has been conducted in the experiment which follows the kinetic modeling.At the end of this research, results will show for the kinetic values for nitrification which are the time taken for the ammonia-N to be reduced,k,and the amount of ammonia-N concentration can be reduced,KN, will be determine to compare and analyze using Linear Regression Method.Lastly,Monod Model represents the growth of the microorganism inside the soil mixed culture which determines the rate of nitrification process. From the experiment that has been done,the results that want to be obtained were for the value of the coefficient k and KN for both the UMP soil mixed culture(UMPC)and poultry farm soil mixed culture(PFC).By using the experimental data obtained in this research, the kinetic constants for nitrification were determined as k = 1.227 h-1 and KN = 67.609 mg/L for UMPC and k = 1.090 h-1 and KN = 68.454 mg/L for PFC.These value of KN and k will determine the maximum reduction of ammonia-N concentration and the time taken for the process. From the result, the best solution in reducing the ammonia-N concentration was by using the PFC because the PFC can reduce the most ammonia-N in lesser time than UMPC. Other than that,the PFC can reduce more ammonia-N than other research which they obtained a lower reduction of ammonia-N concentration and slower time taken to reduce the ammonia-N concentration.